2020
DOI: 10.1136/emermed-2020-209698
|View full text |Cite
|
Sign up to set email alerts
|

Identification of very low-risk acute chest pain patients without troponin testing

Abstract: BackgroundThe HEART Pathway combines a History ECG Age Risk factor (HEAR) score and serial troponins to risk stratify patients with acute chest pain. However, it is unclear whether patients with HEAR scores of <1 require troponin testing. The objective of this study is to measure the major adverse cardiac event (MACE) rate among patients with <1 HEAR scores and determine whether serial troponin testing is needed to achieve a miss rate <1%.MethodsA secondary analysis of the HEART Pathway Implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The recently proposed strategy that a HEAR score less than or equal to 1, 30 independent of troponin, may be appropriate to identify low-risk patients who do not require further cardiac investigation was evaluated post hoc, along with the paramedic clinical interpretation of the history component of the HEART score as low risk in isolation. As requested during the review process, details of the nonadjudicated discharge diagnoses are also presented, as is information regarding those who experienced an important adjudicated endpoint after index hospital discharge, but within 30 days.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The recently proposed strategy that a HEAR score less than or equal to 1, 30 independent of troponin, may be appropriate to identify low-risk patients who do not require further cardiac investigation was evaluated post hoc, along with the paramedic clinical interpretation of the history component of the HEART score as low risk in isolation. As requested during the review process, details of the nonadjudicated discharge diagnoses are also presented, as is information regarding those who experienced an important adjudicated endpoint after index hospital discharge, but within 30 days.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Smith et al used a net reclassification index (NRI) to assess the incremental value of adding a troponin measurement for distinguishing low from high-risk patients [23]. They determined that the addition of a single troponin to a HEAR score of ≤ 1 did not significantly improve risk classification [11]. We did not perform this analysis because only one patient with HEAR ≤ 1 had a 30-day major adverse cardiac event, suggesting minimal incremental benefit of highsensitivity troponin measurement in patients with very low HEAR scores.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Smith et al proposed a modified version of the original HEART score, omitting the troponin component in an attempt to identify patients at such low risk of 30-day major adverse cardiac events that they may not require any biomarker testing at all (Appendix A, Table 4) [11]. In a secondary analysis of data from the HEART Pathway Implementation study [4,12] they tested the prognostic ability of very low HEAR scores in over 4,000 patients with symptoms of possible acute coronary syndromes and no known history of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By design, a troponin result is required for the HEART decision tool 18 to identify patients with an acceptably low rate of major adverse cardiac events (MACE). However, a recent study (n = 4979) 19 found that 9% of patients with HEAR score of 0 to 1 would not need troponin testing to achieve an acceptable MACE rate (<1%); therefore, 9.0% of troponin tests are "medically unnecessary. "…”
Section: Basic Definitions and Assumptionsmentioning
confidence: 99%